Extensions of the Energy PUblic Policy Model for Austria and other European countries E-(PuMA) - Johannes Berger; Ludwig Strohner (EcoAustria - Institute for Economic Research, 2022)
This Research Paper contains a documentation of extensions of the dynamic computable general equilibrium model PuMA to implement energy and greenhouse gas emissions (GHG). The documentation of the PuMA model is published in EcoAustria Research Paper No. 11. Up to now, the model was applied to analyse economic, labour market and public finance effects of different policy reforms, structural changes and other important policy questions. PuMA is similar to the EU Labour Market Model (EU-LMM), which was also developed by the authors and is used by the Directorate General Employment, Social Affairs & Inclusion of the European Commission.1 E-PuMA extends the model by implementing important channels of energy demand of private households and firms as well as GHG emissions. E-PuMA implements additional demand nests for private households. This allows to model the impact of energy price changes on demand and various policy reforms like CO2 related prices. In addition to final goods and investment goods firms additional types of firms are implemented. Electricity firms produce electricity by different kinds of energy inputs and corresponding capital stock and provide electricity to private households and the energy firms. Energy firms combine different energy inputs together with capital and electricity to produce energy provided to final goods firms. Final goods firms demand energy and decide about abatement effort with respect to non-energy-related emissions. Section 2 describes extensions related to private households, Section 3 extensions related to firms, Section 4 describes changes related to functional forms, and Section 5 discusses relevant literature for the calibration of the model.
Keywords: 330